Sustainability of Corporate Social Responsibility Activities - Srivorakan, Korapol; Jarutirasarn, Piyachat; Suesawadwanit, Piyamas (Ph.D. in Social Sciences Journal, 2023)
This academic article aims to study factors influencing the sustainability of social responsibility operations. Using the concept of Triple Bottom Line and Caroll’s CRS Pyramid concept of corporate social responsibility of Buchholz and Catton (1999) and Carroll (1991). Findings are as follows: Factors influencing the sustainability of social responsibility operations include (1) the transformational leadership of executives. The important characteristics of transformational leadership have an influence on the operations of the organization. (2) Marketing orientation that focus on customers are more responsive to society. (3) Building relationships with stakeholders. (4) Corporate governance by a management system that is efficient, transparent, and verifiable. (5) Perception and participation, it provides an opportunity for those involved to perceive information, analyze troubleshooting guidelines, and join together in solving problems. All 5 factors therefore influence the sustainability of the organization’s operations.